Land governance: policy reforms and regional initiatives - Sridhar, C. (ed.); Singh, Varunendra Vikram (ed.); Mishra, Snehasis (ed.) (Mussoorie B. N. Yugandhar Centre for Rural Studies, LBSNAA, 2020)
It was set up in the year 1989 by the Ministry of Rural Development, Government of India, with a multifaceted agenda that included among others, the concurrent evaluation of the ever-unfolding ground realities pertaining to the implementation of the Land Reforms and Poverty Alleviation Programmes in India.
Keywords: Land Governance; IAS as an editor